TDP-43 stabilises the processing intermediates of mitochondrial transcripts - Keiichi Izumikawa; Yuko Nobe; Harunori Yoshikawa; Hideaki Ishikawa; Yutaka Miura; Hiroshi Nakayama; Takashi Nonaka; Masato Hasegawa; Naohiro Egawa; Haruhisa Inoue; Kouki Nishikawa; Koji Yamano; et al. (Scientific Reports, 2017)
Abstract The 43-kDa trans-activating response region DNA-binding protein 43 (TDP-43) is a product of a causative gene for amyotrophic lateral sclerosis (ALS). Despite of accumulating evidence that mitochondrial dysfunction underlies the pathogenesis of TDP-43–related ALS, the roles of wild-type TDP-43 in mitochondria are unknown. Here, we show that the small TDP-43 population present in mitochondria binds directly to a subset of mitochondrial tRNAs and precursor RNA encoded in L-strand mtDNA. Upregulated expression of TDP-43 stabilised the processing intermediates of mitochondrial polycistronic transcripts and their products including the components of electron transport and 16S mt-rRNA, similar to the phenotype observed in cells deficient for mitochondrial RNase P. Conversely, TDP-43 deficiency reduced the population of processing intermediates and impaired mitochondrial function. We propose that TDP-43 has a novel role in maintaining mitochondrial homeostasis by regulating the processing of mitochondrial transcripts.